2007
DOI: 10.1093/ajcn/86.5.1302
|View full text |Cite
|
Sign up to set email alerts
|

Cobalamin and folate status in infants and young children in a low-to-middle income community in India

Abstract: Background: Population-based data on the prevalence of cobalamin and folate deficiency in India are lacking. Objective: The objective was to measure the prevalence of cobalamin and folate deficiency among children aged 6 -30 mo residing in a low-to-middle income community in North India. Design: Children aged 6 -30 mo (n ҃ 2482) were identified through a community survey in a low-to-middle socioeconomic area in New Delhi, India. Non-fasting venous blood samples were collected before enrollment in another trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
83
4
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 44 publications
8
83
4
4
Order By: Relevance
“…Vitamin B-12 status is the most important predictor for plasma tHcy in this population. 3 We found a substantial and significant reduction in tHcy concentration after folic acid or vitamin B-12 supplementation. The excellent compliance was reflected in a threefold increase in plasma folate concentrations.…”
Section: Figurementioning
confidence: 55%
See 1 more Smart Citation
“…Vitamin B-12 status is the most important predictor for plasma tHcy in this population. 3 We found a substantial and significant reduction in tHcy concentration after folic acid or vitamin B-12 supplementation. The excellent compliance was reflected in a threefold increase in plasma folate concentrations.…”
Section: Figurementioning
confidence: 55%
“…[1][2][3] The main source of vitamin B-12 is animal-derived foods, which are expensive and for cultural and religious reasons often not eaten at all. 1 In addition to breast milk, the best sources of folates are dark-green vegetables and legumes.…”
mentioning
confidence: 99%
“…This dietary regimen at least partly explains the magnitude of vit B12 deficiency (49%), and the lower incidence of folic acid deficiency (11%) in this population. More or less the same scenario is observed in different regions and populations in India (Refsum et al, 2001;Yajnik et al, 2006;Taneja et al, 2007;Kumar et al, 2009a, b). It is important to note that even Western and South-East Asian populations do not show such high incidence of vitamin B12 deficiency as seen in Indian populations (Gamble et al, 2005;McLean et al, 2008;Elmadfa and Singer, 2009;Thuesen et al, 2010;Waskiewicz et al, 2010).…”
Section: Hcy-modulation and Micronutrientsmentioning
confidence: 57%
“…There are currently no standard criteria for defining B 12 deficiency in children, but 2·5 % were deficient according to the adult definition and a further 14 % had 'marginal' status. Given that rates of deficiency in India have been measured at 1-44 %, the prevalence in our cohort could be considered low (10)(11)(12)(13)(14) . However the 150 pmol/l cut-off was derived for adults and may not be a valid measure of deficiency for children.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…There is no standard definition of deficiency among children and there is a paucity of data on B 12 status among Indian children. However, recent studies using adult cut-offs have reported that 2-44 % of infants and school-age children are deficient (10)(11)(12)(13)(14) . A study in Pune, India showed normal B 12 absorption in the majority (90 %) of individuals studied (15) .…”
mentioning
confidence: 99%